Analisis Kelayakan Finansial Pola Tanam Berbasis Padi Gogo di Maluku - Agung Budi Santoso; Sheny Kaihatu; Edwin Waas (Jurnal Ilmu Pertanian Indonesia, 2021)
The upland rice-based cropping pattern is a form of double cropping or crop rotation in which upland rice as a basic commodity (base crop) which can be preceded or alternated with other food crops as a secondary crop. This study was conducted on dry land agro-ecosystems in the Tanimbar Islands Regency (West Southeast Maluku), from March to December 2017. This study was an adaptive research with a field experiment approach in farmer's land. The objective of this research was to obtain the most profitable cropping patterns, efficiency in land use and economically also has the highest net profit so it is appropriate to be recommended as a technology innovation for upland rice-based cropping patterns in dry land. The results showed that upland rice which was cultivated in multiple ways through intercropping or overlapped cropping, namely Introduced Cropping Pattern 1 (Upland Rice + Maize-Peanuts) and Introduced Cropping Pattern 2 (Upland Rice + Corn/Cassava-Green Beans-Peanuts) can increase land productivity (index planting of 222% and 288%, respectively) and farmers' income increased by 244-588% compared to upland rice grown in monoculture. Multiple cropping patterns can be recommended as a technology package for upland rice-based cropping patterns on dry land because of its efficiency in the use of production costs and land use. Furthermore, it gave the highest farm income of IDR63,933,100,-/ha/year with a net profit of IDR45,716,380,-/ha/year or IDR15,238,793,-/ha/ cropping season. Keywords: cropping pattern, farming, land use, upland rice